L’e-Government nell’Ue: le conferenze e le best practice - Maddaluno, Paola (Rivista di studi politici internazionali, 2010)
E-Government appears in Public Administration at the end of the Eighties, together with the Internet birth. The European Union, according to the strategy employed in April 2000 also Lisbon has committed itself to provide the citizens with better public services and a better democracy, while the enterprises gained less bureaucracy and more efficiency, therefore promoting e-Government. An Action Plan was adopted with following updates and specific Conferences were organized every two years, from which the best applications of e-Government provided by the administrations were selected and were appointed as best practice. This study is a review of the work of the European Union L’e-Gouvernement est arrivé dans l’Administration publique à la fin des années Quatre-vingts, au même temps que l’Internet. L’Union européenne, après la stratégie adoptée à Lisbonne en avril 2000, est aussi engagée à donner aux citoyens des meilleurs services publiques et une meilleure démocratie, par conséquent aux entreprises moins de bureaucratie et plus d’efficacité, et donc elle soutient le développement de l’e-Gouvernement. Un plan d’action fut adopté avec des ajournements suivants, des conférences chaque deux ans furent organisées, dans lesquelles les meilleures applications de l’e-Gouvernement ont été sélectionnées et identifiées comme best practice. PAROLE CHIAVE: e-Government; Best practice; Unione europea; Lisbona 2000; Internet.